2016
DOI: 10.1089/apc.2015.0318
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Mother-to-Child Transmission of HIV in Option B+ Era: Uptake and Adherence During Pregnancy in Western Uganda

Abstract: Since 2012, lifelong antiretroviral therapy for all HIV-positive pregnant women ("Option B+") is recommended by WHO for the prevention of mother-to-child transmission of HIV (PMTCT). Many sub-Saharan African countries have since introduced this regimen, but to date, longer-term outcome evaluations are scarce. We conducted an observational study in Fort Portal Municipality, Uganda, to describe uptake and adherence of Option B+ during pregnancy. HIV-positive women approaching antenatal care (ANC) services in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 35 publications
3
61
0
Order By: Relevance
“…A national-wide study done in Malawi, looking at facility-level data, found that nearly 24% (95% CI 22.6-25.3%) of women started on ART while pregnant are lost to follow-up in the first 6 months [7]. These findings were consistent with findings of other observational studies done Sub-Saharan Africa in showing the gaps in retaining women on care once initiated on Option B+ [8,9].…”
Section: Challenges Of Implementing Option B+supporting
confidence: 83%
“…A national-wide study done in Malawi, looking at facility-level data, found that nearly 24% (95% CI 22.6-25.3%) of women started on ART while pregnant are lost to follow-up in the first 6 months [7]. These findings were consistent with findings of other observational studies done Sub-Saharan Africa in showing the gaps in retaining women on care once initiated on Option B+ [8,9].…”
Section: Challenges Of Implementing Option B+supporting
confidence: 83%
“…All women were drug naïve at enrolment and received the recommended first-line regimen consisting of EFV/3TC/TDF. Socio-demographic and clinical baseline data, as well as information on the antenatal adherence of the study group were published by Schnack et al, 2016[35]. …”
Section: Resultsmentioning
confidence: 99%
“…Given the strategy’s rapid roll out in the region and the challenges of inadequate adherence and early LTFU highlighted in recent quantitative studies [45,78,10], there is an urgent need to enhance understanding on how to improve ART adherence and retention. Qualitative research is useful for exploring meanings behind quantitative findings [18].…”
Section: Discussionmentioning
confidence: 99%
“…An observational multi-facility cohort study in Malawi had comparable findings of high LTFU (22%) in the first year of implementing Option B+ [5] while a study from one facility in Malawi further clarified that 47% of LTFU women only collected their drugs at the time of initiation but never returned to the same clinic to refill their drugs [6]. Published works from other sub-Saharan African countries also show similar gaps regarding retention in care [78]. Some of the factors associated with LTFU under Option B+ included younger age at initiation, [56,9] being pregnant (compared to lactating) [6], starting ART on the same day of diagnosis [4,7,9], lack of disclosure [7], missing CD4 cell counts at ART initiation [9], having less than a secondary education [7], and receiving care at high volume facilities [45, 9].…”
Section: Introductionmentioning
confidence: 97%